Comparison of commonly used vasopressors for treating hypotension after spinal anaesthesia in elective lower abdominal surgery: a randomized, observational, case-control study - Kumari, Pradeep; Tahir, Sifna; Kumari, Haveena; Mir, Altaf Ahmad (International Journal of Research in Medical Sciences, 2019)
Background: During caesarean section hypotension due to spinal block is secondary to the sympathetic blockade and aorto-caval compression by the uterus. It can have important consequences for the mother and may affect neonatal outcome. The present study was aimed to compare intravenous bolus doses of phenylephrine and ephedrine to treat maternal hypotension during spinal block for elective caesarean section. Methods: After fulfilling the inclusion criteria, 100 parturient were randomly allocated into two groups of fifty each. For spinal anesthesia lumber puncture was done and 12.5mg, 0.5% hyperbaric bupivacaine was given intra-thecally. In this observational study, patients who developed hypotension under spinal anesthesia were selected for the study. According to their group, patients received either ephedrine 6mg (Group E) or phenylephrine 75µg (Group P) as vasopressor. During the study, number of vasopressor boluses, hemodynamic response and time taken to recover from hypotension was noted. Results: Ephedrine and phenylephrine were used in the mean doses of 6.72±1.97mg and 91.5±31.38µg respectively. In 88% parturient single bolus dose of ephedrine was effective in treating hypotension while phenylephrine was effective in 78% parturient. There was no significant difference observed in total number of boluses used. No significant difference was seen in mean systolic blood pressure, mean diastolic blood pressure and mean arterial pressure over a given period of time in Group E and Group P. Mean systolic BP was less than 20% when compared to baseline in both the groups at different time intervals. In Group P the mean heart rate was significantly lower as compared to the Group E (p<0.05). Conclusions: Intravenous phenylephrine and ephedrine are both similar in performance in treating hypotension after spinal anesthesia for elective caesarean section and the hypotensive control offered is comparable.